Circuital characteristics and radiation properties of an UWB electric‐magnetic planar antenna for Ku‐band applications. Issue 1 (27th February 2013) - Haider, N.; Caratelli, D.; Yarovoy, A. G.
<x xml:space="preserve">Abstract</x> A planar, directive antenna with large fractional bandwidth is introduced in this paper. A detailed discussion on the proposed antenna topology and its architecture is reported. The proposed element is a combination of a patch and a loop radiator. A proper combination of the electric field radiator (patch) with a magnetic field radiator (loop around the patch) is exploited for expanding the operational bandwidth. A parametric study is presented to investigate the effect of the antenna geometrical parameters on its performance. A general and computationally efficient procedure for extracting the antenna equivalent circuit is described and used to achieve a meaningful circuit theory‐based insight into the characteristics of the radiating structure. The theoretical and experimental results are compared, and it is demonstrated that the element features over 100% fractional bandwidth, good impedance matching, and unidirectional and stable radiation patterns.